Collaboratively Improving Diabetes Care in Sweden Using a National Quality Register: Successes and Challenges—A Case Study. Issue 4 (October 2015) - Peterson, Anette; Gudbjörnsdottir, Soffia; Löfgren, Ulla-Britt; Schiöler, Linus; Bojestig, Mats; Thor, Johan; Andersson Gäre, Boel
Abstract : Background: Since 1996, the Swedish National Diabetes Register (NDR) enabled health care providers to monitor their clinical performance over time and compare it with the national average. All health systems of Swedish county councils report data. By 2014, the NDR included data from 360 000 patients. Comparisons among county councils show significant variations in clinical outcomes and in adherence to evidence-based national guidelines. The purpose of this study was to evaluate whether and how a quality improvement collaborative could influence clinical practice and outcomes. Methods: Twenty-three diabetes teams from all over Sweden, both primary care units and internal medicine departments, joined a quality improvement collaborative. The project was inspired by the Breakthrough Collaborative Model and lasted for 20 months. Evaluation data were collected from the teams' final reports and the NDR throughout the study period. Results and Conclusion: The teams reported improved patient outcomes significantly compared with the national average for systolic blood pressure and low-density lipoprotein levels. In contrast, glycated hemoglobin A1c levels deteriorated in the whole NDR population. Five themes of changes in practice were tested and implemented. Success factors included improved teamwork, with active use of register data, and testing new ideas and learning from others.